Efficacy of 1% geraniol (Fulltec®) as a tick repellent - Khallaayoune K.; Biron J.M.; Chaoui A.; Duvallet G. (Parasite, 2009)
A field trial on the efficacy of 1% geraniol (Fulltec®) spray against ticks has been carried out in two farms near Rabat (Morocco). Results clearly revealed that 1% geraniol has a preventive effect against Hyalomma ticks. Comparison of geraniol sprayed cows with control herd showed a reduction of mean number of ticks per animal of 98.4%, 97.3% and 91.3% at respectively day 7, 14 and 21 post-spraying. These data give evidence that the geraniol, natural product extracted from plants, could be an alternative to limit use of chemical acaricides, which efficacy is compromised by development of resistance.